Electrical properties of sorbitol‐doped poly(vinyl alcohol)–poly(acrylamide‐co‐acrylic acid) polymer membranes. Issue 6 (12th October 2012) - Josh, Vinitha; Haik, Mohammad Y.; Ayesh, Ahmad I.; Mohsin, Mahmoud A.; Haik, Yousef
Abstract Solid polymer membranes from poly(vinyl alcohol) (PVA) and poly(acrylamide‐co‐acrylic acid) (PAA) with varying doping ratios of sorbitol were prepared using the solution casting method. The films were examined with Fourier transform infrared spectroscopy, thermogravimetric analysis, differential scanning calorimetry, and AC impedance spectroscopy. The impedance measurements showed that the ionic conductivity of PVA–PAA polymer membrane can be controlled by controlled doping of sorbitol within the polymer blends. The PVA–PAA–sorbitol membranes were found to exhibit excellent thermal properties and were stable for a wide temperature range (398–563K), which creates a possibility of using them as suitable polymers for device applications. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013